2007
DOI: 10.3168/jds.2007-0102
|View full text |Cite
|
Sign up to set email alerts
|

Rennet Paste from Lambs Fed a Milk Substitute Supplemented with Lactobacillus acidophilus: Effects on Lipolysis in Ovine Cheese

Abstract: The present work was undertaken to evaluate the effects of Lactobacillus acidophilus supplementation of a milk substitute on the features of lamb rennet paste used for cheese making. Lipolysis in cheese manufactured with rennet paste from lambs receiving supplemented milk was also evaluated. Lambs were subjected to 3 different feeding regimens (mother suckling, MS; artificial rearing, AR; and artificial rearing with 7 log10 cfu/mL of Lb. acidophilus supplementation of the milk substitute, ARLb) and slaughtered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
1
6
1
1
Order By: Relevance
“…These data confirmed the ability of Lb. acidophilus to increase lipolytic activity of rennet paste according to Santillo et al (2007) and highlighted that also B. longum and B. lactis are able to contribute to lipase activity in rennet paste.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data confirmed the ability of Lb. acidophilus to increase lipolytic activity of rennet paste according to Santillo et al (2007) and highlighted that also B. longum and B. lactis are able to contribute to lipase activity in rennet paste.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative strategy to improve the nutritional value of dairy products is the incorporation of probiotic CLA-forming cultures into cheese to increase CLA concentration in the human diet (Van Nieuwenhove et al, 2007). In a previous study, Santillo et al (2007) showed an increase in CLA levels in cheese produced using lamb rennet paste obtained from lambs fed milk substitute contain-ing Lactobacillus acidophilus. Many experiments have been conducted to assess the ability of Bifidobacterium species to produce CLA (Coakley et al, 2003;Oh et al, 2003); however, little is known about the possibility to ameliorate the lipolytic profile of cheese by using probiotic cultures.…”
Section: Introductionmentioning
confidence: 99%
“…2009). Probiotic micro‐organisms added to the diet of suckling lambs (Santillo et al. 2007a,b) resulted in an increase of the enzymatic activity of rennet paste, especially as regards the lipases.…”
Section: Chemistry and Production Technologymentioning
confidence: 99%
“…However, the CLA content of Greek cheese and dairy products is variable . The use of different starter cultures, processing and aging period are factors that may affect CLA content of cheese. However, the influence of aging is still under investigation.…”
Section: Introductionmentioning
confidence: 99%